Regulation of Cell Adhesion Strength by Peripheral Focal Adhesion Distribution - Elineni, Kranthi Kumar (The Biophysical Society, 2011)
Cell adhesion to extracellular matrices is a tightly regulated process that involves the complex interplay between biochemical and mechanical events at the cell-adhesive interface. Previous work established the spatiotemporal contributions of adhesive components to adhesion strength and identified a nonlinear dependence on cell spreading. This study was designed to investigate the regulation of cell-adhesion strength by the size and position of focal adhesions (FA). The cell-adhesive interface was engineered to direct FA assembly to the periphery of the cell-spreading area to delineate the cell-adhesive area from the cell-spreading area. It was observed that redistributing the same adhesive area over a larger cell-spreading area significantly enhanced cell-adhesion strength, but only up to a threshold area. Moreover, the size of the peripheral FAs, which was interpreted as an adhesive patch, did not directly govern the adhesion strength. Interestingly, this is in contrast to the previously reported functional role of FAs in regulating cellular traction where sizes of the peripheral FAs play a critical role. These findings demonstrate, to our knowledge for the first time, that two spatial regimes in cell-spreading area exist that uniquely govern the structure-function role of FAs in regulating cell-adhesion strength.